The Influence of PMM Literacy and Teacher Learning Leadership on Teacher Performance: The Mediating Role of Professional Learning Community Effectiveness - Purwanti, Heni Agus; Asrori, Asrori; Oktarina, Nina (Universitas Negeri Semarang, 2025)
This study is motivated by the need to improve the quality of learning, as indicated by the Indonesian Education Report Card in 2024. PMM (Platform Merdeka Mengajar) is a digital platform designed to support teachers in implementing the Merdeka Curriculum in Indonesia. The study aims to examine the influence of PMM literacy and teacher learning leadership on teacher performance, with Professional Learning Community (PLC) effectiveness serving as a mediating variable. Data were collected from 321 teachers, selected from a population of 1,626 teachers at public junior high schools in Kendal Regency, Indonesia. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS), employing SmartPLS 4.1 as the analysis tool. The results suggest that PMM literacy and PLC effectiveness have direct effects on teacher performance, while teacher learning leadership does not have a direct effect. However, both PMM literacy and teacher learning leadership have significant indirect effects on teacher performance through PLC effectiveness. This study highlights the practical need to support PLC to promote PMM literacy and teacher learning leadership, in order to enhances teacher performance